Pengaruh Variasi Volume Dan Bentuk Saluran Penambah (RISER) Terhadap Hasil Coran Alumunium - Wicaksono, Dhimas; , Patna Partono, ST, MT (2016)
This study aims to determine the effect of volume and shape of the channel adder (riser) of the shrinkage defects, defects of porosity, hardness and examining the content of the elements contained in the aluminum alloy casting process using wet sand molds. In this study, aluminum raw material comes from the former aluminum motorcycle parts. Channel adder (riser) used to have the same volume but different shapes. Adder channel size variation tubular neck (neck) diameter 20 mm and height 10 mm. Variations in the size of the channel adder (riser), namely: a diameter of 40 mm with a height of 20 mm, and 20 mm diameter by 80 mm high. shrinkage testing by comparing the volume of products with mold volume. Observations cavity cast product shrinkage by splitting it into two parts. Testing with the test density porosity, macro and micro observations photo. Testing Brinell hardness using portable test equipment. The casting process is used with sand mold casting. Based on the results of testing for chemical composition that is obtained is found to chemical element (Al) 91.60%, silicon (Si) 2:51%. While other elements less (<2%), namely Carbon (C) 1.95%, Pb 1.79%, and other elements that are less (<1%), namely Magnesium (Mg) 12:32%, Titanium (Ti) 12:25%, iron (Fe) 12:51%, 0,24% Cu, Zinc (Zn) 0.81%, Stanum (Sn) of 0.03%. So from the elements present this material include metal aluminum silicon alloy (Al-Si). The percentage value of depreciation for the variation I without a riser at 5.078%, for variation II Small Riser amounting to 3.382%, and for the third variation of the Riser of 2.804%. Results of the study showed that the greater shrinkage of the smaller riser rate depreciation. In testing the microstructure can be concluded that the variation without riser harder for quick cooling and the grain tends to be small and tight. While variations riser small and large riser tend to be more brittle because of the cooling time and the grain looks almost as great.